Associations Between Arterial Stiffness Indices and Chronic Kidney Disease Categories in Essential Hypertensive Patients. (8th October 2020) - Kusunoki, Hiroshi; Iwashima, Yoshio; Kawano, Yuhei; Ohta, Yuko; Hayashi, Shin-ichiro; Horio, Takeshi; Shinmura, Ken; Ishimitsu, Toshihiko; Yoshihara, Fumiki
Abstract: BACKGROUND: This study investigated the association between arterial stiffness indices and asymptomatic chronic kidney disease (CKD) risk categories in hypertensive patients. METHODS: Arterial stiffness indices, including 24-hour brachial and aortic systolic blood pressure (SBP) and pulse wave velocity (PWV), were measured by an oscillometric Mobil-O-Graph device, brachial-ankle PWV (baPWV) by a volume-plethysmographic method, and renal resistive index (RI) by ultrasonography, in 184 essential hypertensive patients (66.0 ± 17.1 years, 47.3% male). CKD was categorized into 3 stages based on the Kidney Disease Improving Global Outcomes (KDIGO) criteria, using a combination of estimated glomerular filtration and albuminuria. RESULTS: The 24-hour aortic PWV (aPWV), baPWV, and RI increased with worsening severity of CKD risk category (all P < 0.01 for trend). Multivariate logistic regression analysis found that a 1 SD increase of nighttime aortic SBP (odds ratio [OR] 1.52), PWV (OR 4.80), or RI (OR 1.75) was an independent predictor of high or very-high CKD stage (all P < 0.05). After adjustment for potential confounders, day-to-night change in brachial SBP as well as in aPWV differed among groups ( P < 0.05, respectively). In a multivariate regression model, day-to-night changes in aortic SBP and PWV, and RI were independently associated with day-to-night brachial SBP change. CONCLUSIONS: In hypertension, circadian hemodynamics in high CKD stage are characterized by higher nighttime values of aortic SBP and PWV and disturbed intrarenal hemodynamics. Further, the blunted nocturnal BP reduction in these patients might be mediated via disturbed intrarenal hemodynamics and circadian hemodynamic variation in aortic SBP and arterial stiffness.